Proceedings of the Seventeenth Annual ACM-SIAM Symposium on Discrete Algorithm - SODA '06 2006
DOI: 10.1145/1109557.1109669
|View full text |Cite
|
Sign up to set email alerts
|

Improved lower bounds for embeddings into L1

Abstract: Abstract. We improve upon recent lower bounds on the minimum distortion of embedding certain finite metric spaces into L 1 . In particular, we show that for every n ≥ 1, there is an n-point metric space of negative type that requires a distortion of Ω(log log n) for such an embedding, implying the same lower bound on the integrality gap of a well-known semidefinite programming relaxation for sparsest cut. This result builds upon and improves the recent lower bound of (log log n) 1 1. Introduction. In recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 16 publications
(35 reference statements)
2
59
0
Order By: Relevance
“…The hypercube example appears to be a serious obstacle to improving the approximation factor for finding sparse cuts, since the optimal cuts of this graph (namely, the dimension cuts) elude all our rounding techniques. In fact, hypercube-like examples have been used to show that this particular SDP approach has an integrality gap of Ω(log log n) (Devanur et al [2006;Krauthgamer and Rabani [2006]). …”
Section: · 113mentioning
confidence: 99%
See 1 more Smart Citation
“…The hypercube example appears to be a serious obstacle to improving the approximation factor for finding sparse cuts, since the optimal cuts of this graph (namely, the dimension cuts) elude all our rounding techniques. In fact, hypercube-like examples have been used to show that this particular SDP approach has an integrality gap of Ω(log log n) (Devanur et al [2006;Krauthgamer and Rabani [2006]). …”
Section: · 113mentioning
confidence: 99%
“…Originally it was suggested in Goemans [1998] that the SDP with triangle inequality has an integrality gap of O(1) but Khot and Vishnoi [2005] showed that the gap is Ω(log log 1/6 n), which was improved to Ω(log log n) by Krauthgamer and Rabani [2006] for the nonuniform sparsest cut. Recently, Devanur et al [2006] showed that the Ω(log log n) gap holds even for the uniform version.…”
Section: Lemma 29 (Flows As Dual Solutions)mentioning
confidence: 99%
“…The question of (non-)embeddability of edit distance into 1 appears on the Matoušek's list of open problems [Mat07], as well as in Indyk's survey [Ind01]. From the first nonembeddability bound of 3/2 of [ADG + 03], the bound has been improved to Ω(log 0.5−o(1) d) by Khot and Naor [KN06], and later to the state-of-the-art Ω(log d) bound of Krauthgamer and Rabani [KR06]. Later, Andoni and Krauthgamer [AK07] prove an Ω( log d log log d ) lower bound for embedding into more general classes of spaces, which includes 1 .…”
Section: Introductionmentioning
confidence: 99%
“…This has been a rather unique approach to the construction of counterexamples in metric geometry. The lower bound was improved to Ω(log log n) by Krauthgamer and Rabani [27], and shortly afterward Devanur, Khot, Saket, and Vishnoi [18] showed that even the Sparsest Cut relaxation has an integrality gap Ω(log log n).…”
Section: Semidefinite Programming and Uniquementioning
confidence: 99%